Professor, Centre for Management Studies, Jamia Millia Islamia (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2021)
The basic purpose of this study was to evaluate  the strategic planning practices by Financial  Sectors and how owners and managers of  these Financial Sectors play their roles in it  in Tanzania. The other study objective was to  ascertain if differences in strategic planning  practices existed with respect to Strategic  Planning in Tanzania’s Financial Sectors. The  study discovered the main scopes of strategic  planning are environmental scanning, mission  and vision, implementation incentives, time  horizon of strategic planning, evaluation and  control, employee involvement in strategic  planning, the structure of strategic planning as  well as source of information concerning the  environment. Consequently the study discovered  that vision and mission, a formality of strategic  planning and evaluation and control were the  most valued factors. The study concluded that  there is insignificant statistical difference among  managers and owners in their positions during  strategic planning process. The study offers  various dimensions of strategic planning that  Financial Sectors of Tanzania can implement to  be competitive and sustainable.
Keywords: Financial Sectors; strategic planning; evaluation; monitoring; motivation; growth; planning barriers; Vision; Mission; Tanzania